Antofine Triggers the Resistance Against Penicillium italicum in Ponkan Fruit by Driving AsA-GSH Cycle and ROS-Scavenging System - Peng, Xuan; Zhang, Yanan; Wan, Chunpeng; Gan, Zengyu; Chen, Chuying; Chen, Jinyin (Frontiers in Microbiology, 2022)
Postharvest fungal infection can accelerate the quality deterioration of Ponkan fruit and reduce its commodity value. Penicillium italicum is the causal pathogen of blue mold in harvested citrus fruits, not only causing huge fungal decay but also leading to quality deterioration. In our preliminary study, antofine (ATF) was found to have a great potential for significant in vitro suppression of P. italicum growth. However, the regulatory mechanism underpinning ATF-triggered resistance against P. italicum in citrus fruit remains unclear. Here, the protective effects of ATF treatment on blue mold development in harvested Ponkan fruit involving the enhancement of ROS-scavenging system were investigated. Results showed that ATF treatment delayed blue mold development and peel firmness loss. Moreover, the increase of electrolyte leakage, O2•– production, and malonyldialdehyde accumulation was significantly inhibited by ATF treatment. The ATF-treated Ponkan fruit maintained an elevated antioxidant capacity, as evidenced by inducted the increase in glutathione (GSH) content, delayed the declines of ascorbic acid (AsA) content and GSH/oxidized GSH ratio, and enhanced the activities of superoxide dismutase, catalase, peroxidase, and six key AsA-GSH cycle-related enzymes, along with their encoding gene expressions, thereby maintaining ROS homeostasis and reducing postharvest blue mold in harvested Ponkan fruit. Collectively, the current study revealed a control mechanism based on ATF-triggered resistance and maintenance of a higher redox state by driving AsA-GSH cycle and ROS-scavenging system in P. italicum-infected Ponkan fruit.